Effect of Body Weight on Metabolic Hormones and Fatty Acid Metabolism in Follicular Fluid of Women Undergoing In Vitro Fertilization: A Pilot Study. (March 2019) - Bou Nemer, Laurice; Shi, Haolin; Carr, Bruce Richard; Word, Ruth Ann; Bukulmez, Orhan
Introduction: Obesity is an epidemic affecting more than one-third of adults in the United States. Obese women experience decreased fertility, explained in part by oocyte quality. Since follicular fluid (FF) provides an important microenvironment for oocyte growth, we sought to evaluate the effect of increased body weight on FF levels of 11 metabolic hormones and fatty acid metabolism. Methods: The FF was collected from 25 women (10 normal weight, 10 overweight, and 5 obese) with diminished ovarian reserve undergoing in vitro fertilization (IVF) following a minimal stimulation protocol. Hormone levels were determined by multiplex immunoassay using the MAGPIX (Luminex, Austin, Texas) instrument. Fatty acid metabolites were determined using gas and ultra-high pressure liquid chromatography coupled with mass spectrometry. Results: Levels of hormones related to glucose and energy homeostasis and regulation of fat stores (insulin, glucagon, glucagon-like peptide-1, C-peptide, and leptin) were increased significantly in FF from obese women compared to FF from nonobese(normal weight and overweight) women. Interestingly, FF levels of branched-chain amino acids (BCAA) isoleucine, leucine, and valine as well as uric acid, isocaproic acid, butanoic acid, tyrosine, threonine, glycine, and methionine correlated positively with body mass index. Conclusion: This pilot study demonstrates significant alterations in the FF milieu of obese women undergoing IVF, which may contribute to the decreased fecundity of obese women. Although the impact of this environment on oocyte and embryo development is not fully realized, these changes may also lead to imprinting at the genomic level and long-term sequelae on offspring.